The potential risk of Schistosoma mansoni transmission by the invasive freshwater snail Biomphalaria straminea in South China - Lin, DaTao; Zeng, Xin; Sanogo, Benjamin; He, Ping; Xiang, Suoyu; Du, Shuling; Zhang, YanHua; Wang, Lifu; Wan, Shuo; Zeng, XingDa; Yang, Ya; Lv, ZhiYue; et al. (PLOS Neglected Tropical Diseases, 2020)
Author summary Biomphalaria straminea is an important intermediate host for the blood fluke Schistosoma mansoni. B. straminea has spread in Hong Kong and in mainland China since 1973. However, whether resident snails can transmit intestinal schistosomiasis caused by S. mansoni remains unclear. Our results revealed that different types of B. straminea are widespread in cities such as Hong Kong, Shenzhen, Dongguan, Huizhou and Puning and that the distribution of the species has shifted northwards. The most important finding was that one of the phenotypes (red phenotype of B. straminea, RBS), which is highly susceptible to S. mansoni, has spread into the city of Shenzhen since 2016. The density of RBS in Guangdong Province has increased rapidly since 2014, especially since 2016. Transcriptome analysis showed that the high expression levels of ficolin, C1q, MASP-like, and membrane attack complex (MAC)/perforin models of the complement system might be associated with the mechanism of susceptibility. Our study suggested that B. straminea is susceptible to S. mansoni, implying a high potential risk of S. mansoni transmission in South China. More attention should be paid to the potential transmission of S. mansoni, and control measures should be established to prevent the spread of this snail in South China.